Bacteriostatic effect of copaiba oil (Copaifera officinalis) against Streptococcus mutans - Pieri,Fábio Alessandro (2012)
This study evaluated the inhibitory activity of copaiba oil (Copaifera officinalis against the cariogenic microorganism, Streptococcus mutans. For such purpose, a minimum inhibition concentration test of copaiba oil against S. mutans was performed, using the serial dilution in broth technique, with a negative control, a positive control (0.12% chlorhexidine) and a 10% copaíba oil solution as a test. A minimum bactericidal concentration test with tubes presenting microbial inhibition was also conduced. In the minimum inhibitory concentration test, copaiba oil showed inhibition of bacterial growth at all concentrations tested up to 0.78 µL/mL of the 10% copaiba oil solution in the broth. In addition, the negative control had no inhibition, and the 0.12% chlorhexidine solution was effective up to 6.25 µL/mL in the broth. Copaiba oil showed a bacteriostatic activity against S. mutans at low concentrations, and could be a an option of phytotherapic agent to be used against cariogenic bacteria in the prevention of caries disease.